Safety and Efficacy of Bipolar Versus Monopolar Transurethral Resection of the Prostate: A Comparative Study - Hirik, Erkan; Bozkurt, Aliseydi; Karabakan, Mehmet; Aydemir, Huseyin; Aktas, Binhan Kagan; Nuhoglu, Baris (Urology Journal, 2015)
Purpose: Transurethral resection of the prostate (TURP) is considered gold standard for surgical treatment of benign prostatic hyperplasia (BPH). In this study, we aimed to compare post-operative clinical outcomes and adverse effects between monopolar and bipolar TURPs. Materials and Methods: The study included 590 patients who underwent TURP by a single urologist (E.H.) between June 2006 and June 2014 with a diagnosis of BPH. Patients were divided into two groups as monopolar TURP (group 1, n = 300) and bipolar TURP (group 2, n = 290). Patients receiving oral anticoagulants or aspirin and those with prostate cancer diagnosis were not included in the study. Data regarding pre-operative age, International Prostate Symptom Score (IPSS), maximum urinary flow rate (Qmax), post voiding residual urine volume (PVR), serum prostate specific antigen (PSA) levels and prostate volume (Vp) of the patients were gathered from medical records. Groups were compared in terms of catheterization, operation time, hemoglobin (Hb) decrease, and IPSS, Qmax, and PVR values at post-operative 12th month follow-up visit. Results: From pre-operative to post-operative period, IPSS, Qmax and PVR showed significant improvements within both groups (P < .001). When groups were compared with each other, bipolar TURP group had significantly lesser catheterization time and hemoglobin decrease than monopolar TURP group, while no significant differences were detected regarding all other variables. Conclusion: Bipolar and monopolar TURPs are both effective and safe treatment modality for BPH. Bipolar TURP is superior to conventional monopolar TURP in terms of catheterization time and Hb decrease.